Effectiveness of antiviral treatment of patients with chronic hepatitis C GT 1b depending on the presence of comorbid chronic renal insufficiency - H. V. Venytska; O. V. Riabokon (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The aim of the work was to analyze the effectiveness of antiviral therapy (3D mode) in patients with chronic hepatitis C (CHC) GT1 in clinical practice, depending on the presence of comorbid chronic renal insufficiency stage V, who receiving hemodialysis.